MEMBANGUN BUDAYA ORGANISASI DALAM PERSPEKTIF NIALI-NILAI ISLAMMEMBANGUN BUDAYA ORGANISASI DALAM PERSPEKTIF NIALI-NILAI ISLAM - Muhammad Husni (Fakultas Agama Islam Universitas Billfath, 2015)
Islamicas a religionsofhavingstandardsandnormsas a referencevaluefollower. The valuesderivedfrom thedoctrinesof religionswashitcertainlycanbe appliedlive the lifeof the daily, includingin the organization. Howeverislamicvalues inanything that canbe usedin buildingthe organizationandhow toimplementthese values. Organizational cultureis builtwitha setthe with ofvaluethatsurebyallbehaviorinan organization ofit. Islamicasasourceprocedureslsohavethe valuesthatcanbe usedasbuilding astrong the organizational of culture. The valuesin the organizationis alsorequiredto bindingandeveryoneinthe organization to aunified whole.